The concept of “historical time” in modern liberal Islam: from the philosophy of temporality to the policy of memory - Maksym Kirchanov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
In this article, the author examines the main features of the perception of historical time in the Arab, Iranian and Indonesian Muslim intellectual traditions in a comparative perspective. The purpose of the article is to analyze the images of "historical time" and its derivatives in the modern liberal segment of the Ummah. Therefore, the author analyzes 1) the peculiarities of the perception of historical time by liberal Muslim intellectuals, 2) the directions of assimilation of Western humanitarian methodology, 3) the prospects for transforming the perception of historical time in the modern humanitarian situation through the prism of rising interdisciplinarity. The article shows that 1) the liberal trend in the ummah demonstrates a wide range of perception of historical time, 2) historical time in Islam is perceived pluralistically, 3) the interpretation of historical time in liberal Islam is dependent on the cultural characteristics of the ummah. Methodologically, the article is based on the principles proposed in interdisciplinary historiography, proposed in intellectual history and new cultural history through the prism of imaginative and interventionist turns. The novelty of the study lies in the analysis of common and unique features of the perception of historical time and its derivatives by modern Muslim liberal intellectuals. The results of the study suggest that 1) Islam has become an important factor in the perception of "historical time", 2) the categories of “event history” and “historical progress” are reduced to the history of the progressive development and spread of Islam, 3) the transplantation of Western interdisciplinary epistemology has become an important factor in the invention of historical time. In general, the article shows that historical time is perceived as a symbolic space for localizing the key moments of the historical memory of the Muslim Ummah. The author believes that the imagination of historical time through the prism of modernity reduces history to the actual present, perceived in terms of the realization of the mission of Islam, associated with the achievement of its global dominance.